Perspektif Hukum Ekonomi Syariah Tentang Jual Beli Viewers Di Instagram - Gaussian, Gini; Taufiqurrohman, Rega; Setiawan, Deri (Jurnal Hukum Ekonomi Syariah, 2025)
Buying and selling viewers is a new trade model whose legal aspects need to be studied in depth. abstract form in the form of additional viewers on accounts on Instagram social media. The problem that arises is how is the mechanism in the practice of buying and selling viewers? Then, in this research will be carried out Then, in this study, an in-depth analysis of the practice of buying and selling viewers on Instagram social media will be conducted. from the perspective of Sharia Economic Law, especially the type of contract used, on the subject of law, legal object, and the contract agreement (ijab and kabul). Type of research used in this thesis is field research. ( Research ). The nature of this research is descriptive analysis. In this research This research is described and analyzed to draw conclusions and legal status about the sale and purchase of viewers on Instagram. about buying and selling viewers on social media instagram. After research is conducted, it can be concluded that buying and selling viewers on Instagram social media can be categorized as buying and selling salam,  Keywords : Shari’ah Economic Law, Buy and Sell, Viewers